Construing domain knowledge via terminological understanding - Kerremans, Koen; Temmerman, Rita; De Baer, Peter (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This article will focus on the process of understanding terms, which is es-sential for translators to propose suitable translations and for terminologists to develop different types of terminological resources. We will discuss how a shift from meaning to understanding has changed our view with respect to the interaction between symbols (i.e. terms), thoughts and referents. Next, we will demonstrate how this view has been applied in termontography, a methodology set up to develop ontologically-underpinned terminological resources, based on the analysis of specialised texts. We will concentrate on the categorization framework, a concept used in termontography for structuring terminological information, and discuss how this framework is currently implemented in a didactic software tool, called CatTerm, which guides student translators to construct a knowledge model of a given domain.